Reflections on the impact of “la patria Boba”, the independence of Tunja and its province 1810-1815 - Robayo, Juan Manuel (Universidad Pedagógica y Tecnológica de Colombia, 2010)
This article aims at reflecting on the first stage of the process of emancipation, developed since 1810 which is considered the starting point of a political project. Building up this project was not easy, it entailed frictions among different political intensions. On this assert we mean the federalism and the idea of the centralism which originated a great disorganization of political and civil elements and the break down and anarchy of six or seven republics apparently linked by a federal pact and a few provinces which defended the peninsular power.The provinces in the interior of the country faced situations of instability in their political life, born from the indecision to choose a unique criterion in terms of the political and administrative management of their territories. Referring to the Federal government adopted in the province of Tunja, it is emphasized on the necessity of promoting the total independence from the Spaniard system, due to the poverty of the people, the lack of public schools and the need of fomenting agricultural production and trade. However, this political project did not reach the goals its leaders estimated, first because the participation of the ‘criollos’ in the public administration was not as easy as expected. The second reason was that, as a result of the segregation of the provinces, a crisis was evidenced when the unified basis of tax collection stopped working. The third issue was due to the fact that territorial segregation became one of the greatest difficulties for the correct political-administrative organization, it is necessary to highlight that the join of some towns, and sometimes complete regions from one province to the other, made difficult tax collection.